KNOWLEDGE, ATTITUDE AND PRACTICE OF MOTHERS REGARDING THEIR OWN AND CHILDREN'S DENTAL HEALTH-A TERTIARY CARE HOSPITAL BASED STUDY - Farid, Huma; Khan, Farhan Raza; Aman, Nadia (Journal of Ayub Medical College Abbottabad, 2013)
Background: Mothers play a basic role in the dental health of children. They decide whether their children need dental treatment or not. The aims of this study were to assess mothers' knowledge and practices regarding children's dental health and to determine association of mothers own attitude and their attitude towards children's dental health. Methods: A cross sectional study was conducted in the Aga Khan University Hospital (AKUH), Karachi, Pakistan in which 207 mothers completed a self-administered structured questionnaire. Inclusion criteria were respondents having children between 2 and 5 years of age and exclusion criteria were respondents having physical or mentally handicapped children. SPSS-16 was used for data analysis. Chi Square test was used to determine association between maternal own dental attitude and their attitude and knowledge about children dental health with p‰¤0.05 as statistically significant. Results: Majority of the mothers used to visit dentists for themselves in the case of problems and they thought the same for their children (p<0.001). A statistically significant association also existed between mothers and children tooth brushing frequency (p<0.001). Conclusions: Mothers visitingAga KhanUniversityHospital, lack sufficient knowledge regarding timings of the children's first dental visit and the importance of limiting frequency of in-between meals snacks consumed by their children. Keywords: Mothers' dental health, children dental health, dental visit, knowledge